The Reality of financial Autonomy of local communities and Its Impact on local Development: “A Case Study of a Group of Municipalities in Boumerdes province - khalfi, nora; yahiaoui, Ahmad (Journal of Research in Finance and Accounting, 2024)
The enjoyment of local communities of legal personality and administrative autonomy, in light of the embodiment of local democracy according ti the applicable legislation, also necessitates the recognition of financial independence. This implies the provision of stable self-financing resources that ensure the success of their role in promoting local development and enable them to perform their assigned responsibilities. However, the issue of self-financing for municipalities is one of the greatest obstacles facing local governance systems, hindering their ability to achieve local development. This study aims to analyze the reality of financial autonomy among several Algerian municipalities and its relationship to local development. The study concluded that Algerian municipalities still contribute very little of their own resources to financing local development, as most development projects heavily rely on grants and transfers from the central administration. The reality indicates that the self- generated revenues of local communities are insufficient even to cover basic operating expenses, reflecting the weak financial independence of Algerian municipalities and their limited capacity to achieve sustainable local development without relying on financial transfers from the central authority.